Виндоуз или Windows? Кириллица и латиница в названиях торговых марок (на материале современных русских художественных текстов) - Prokopczuk, Klaudia A. (Acta Neophilologica, 2019)
This paper discusses the usage principles of Cyrillic and Latin scripting for foreign-lan-guage commercial names in Russian fiction in the late 20th and early 21st centuries. These include the following factors: the existing tradition concerning the employment of foreign language words in Russian texts; the possibility of employing different fonts as means of indirect valuation and of indication that the speech subject belongs to a certain social group, as well as stylistic and morphologic factors related to a possibility (or impossibility) for a trade mark to obtain Russian case endings; the iconic function of a font; a language game.